ANTIMICROBIAL ACTIVITY OF BACTERIAL CELLULOSE MODIFIED WITH PLANT EXTRACTS - Riza Apriani; Nina Utami (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Bacterial cellulose (BC) is utilized in numerous industries, including the cosmetic, biomedical, and packaging industries. Nonetheless, BC lacks antibacterial activity and must be combined with antimicrobial agents, including plant extracts. This review aims to give information on the antibacterial activity of BC that has been modified by the addition of plant extracts. The method used in this study is article review. Articles were selected from Q1-Q3 category international journals published within the recent decade. Based on the results, extracts of rhizomes, ethanol extracts of gwarri stems and leaves, oregano leaves, rosemary leaves, lovage leaves, parsley leaves, green tea leaves, rosella petals, and red and pink variants of hibiscus flowers, bitter melon seeds, gletang leaves, arabica coffee, and andaliman fruit, temu Kunci dimethyl sulfoxide extract, mulberry leaf NaOH extract, pomegranate skin water extract, and rosemary leaves have been used to modify BC. Antimicrobial activity showed the most significant increase in BC-modified ethanol extract of rosella petals at a concentration of 500 ppm with an OD600 of 0% against Pseudomonas aeruginosa. FTIR and SEM investigations of pure BC and BC modified with plant extracts revealed variations in functional group content and three-dimensional fibrillar network structure.